Congenital herpes infection: An unusual presentation - Mina, Shyam Sundar; Eske, Gunvant Singh; Kashyap, Archana (Indian Journal of Child Health, 2016)
Maternal genital herpes is a sexually transmitted infection, asymptomatic in 70% of cases. Mostly infection is acquired during intrapartum period or postnatally through contact with mucocutaneous lesions. Primary neonatal herpetic infection outside the oral cavity is uncommon, but there are well-documented ocular cases, with or without associated oral lesions. A high index of clinical suspicion is the key for early antiviral treatment initiation and better outcome.